Iron regulation of the cloned diphtheria toxin promoter in Escherichia coli. - Tai, S P (1988)
Regulation of the diphtheria toxin promoter by iron was studied in Escherichia coli by using a galK transcriptional fusion. A fragment of the toxin (tox) operon containing the regulatory region was cloned from corynephage beta into a galK transcription vector such that expression of galK activity was controlled by the tox promoter. When E. coli N100 (a galK mutant) harboring this tox-galK fusion plasmid was grown in Luria broth, the specific activity of galactokinase remained constant throughout the exponential phase of growth. When bacteria were shifted from such high-iron medium into low-iron Luria broth, the specific activity of galactokinase increased rapidly, but induction of galactokinase was prevented by the addition of iron to the medium. Measurement of tox-specific mRNA by dot blot hybridization showed that this regulation occurred at the level of transcription. When the plasmid containing the tox-galK fusion was introduced into a fur mutant of E. coli, expression of galK was maximal in both high-iron and low-iron media; but repressibility of galK by iron in this strain was restored by complementation with the fur+ allele. The tox promoter has significant homology with the consensus sequence for other iron-regulated promoters of E. coli that are controlled by fur. These data indicate that the product of the fur gene can function in E. coli as an iron-dependent repressor for the tox promoter from corynephage beta.